The The Influence Of Training And Recruitment On Employee Performance In The Marketing Division Of Pt. Bersama Era Sentosa Tama Lumajang - Adinda Regita Puspitasari; Mei Retno Adiwati (Economics and Digital Business Review, 2026)
At PT. Bersama Era Sentosa Tama, a distribution business operating out of Lumajang, East Java, a three-year decline in sales-target achievement raised questions about whether training and recruitment practices in the marketing division were keeping pace with what the job required. This paper sets out to test that link empirically. Fifty marketing-division staff the entire population, surveyed through Google Forms rather than a sample supplied the data behind a quantitative, cause-and-effect analysis processed with SmartPLS under the SEM-PLS framework. Reliability and validity checks cleared every threshold: outer loadings stayed above 0.70, AVE above 0.50, and Composite Reliability above 0.70 across all constructs. Where the two predictors diverged was in their statistical weight. Training moved the needle on performance in a way that held up under testing (path coefficient 0.529, t = 2.900, p = 0.004); recruitment pointed the same direction but fell short of significance (path coefficient 0.201, t = 0.878, p = 0.381). Combined, training and recruitment account for just under half the variance observed in performance (R² = 0.499). The practical takeaway: training carries more weight than recruitment in moving marketing-division performance, so recruitment gains are best treated as a starting point rather than an endpoint, with ongoing development picking up where hiring leaves off.